Collection and morphological characterization of 149 accessions of achiote (Bixa orellana L.) from seven departments in Perú - Nolasco Chumpitaz, Juan Luis; Ccoyllo Llacsa, Paul Andersson; Koc Sanchez, Gabriela Elena; Medina Morales, Percy Edilberto (Universidad Nacional Agraria La Molina, 2023)
The aim of this study was to characterize and identify groups of achiote (Bixa orellana L.) with characteristics related to increased yield and bixin content. A total of 149 achiote accessions were collected from the departments of Loreto, San Martin, Junín, Pasco, Huánuco, Ucayali, and Cusco, in Perú. These were then evaluated using ten quantitative and three qualitative capsule and seed descriptors. Undesirable characteristics such as high spinosity and dehiscence predominated, while none of the quantitative descriptors correlated significantly with bixin content. Principal component analysis indicates that the quantitative descriptors (except for bixin content) are statistically significant, forming four clusters. Notably, one of the clusters included accessions characterized by heavy seeds, and another cluster included accessions with high number of seeds and bixin content.